What Happened to Village lnfrastructure and Public Services During the Economic Crisis in Indonesia? - Darja, Jesse; Suryadarma, Daniel; Suryahadi, Asep; Sumarto, Sudarno (Economics and Finance in Indonesia, 2005)
.